Determinants Of Antipsychotic Drugs Prescription Among Community-Living Older Adults With Dementia: A Population-Based Study Using Health Information Systems In The Lazio Region, Italy - Bargagli, Anna Maria (Clin Interv Aging, 2019)
INTRODUCTION: Despite recommendations from associations of geriatric and psychiatry societies and warnings from drug agencies, antipsychotic (AP) drugs are frequently used to control behavioral and psychological symptoms of dementia. APs are associated with a range of potential adverse events, including increased risk of cerebrovascular events and mortality. Evidence suggests limited efficacy of APs for aggression and psychosis. Our objectives were to investigate patterns and predictors for prescription of APs among older adults with dementia residing in a large region of central Italy, and to identify patient characteristics related to typical or atypical APs prescribing. METHODS: This is a retrospective population-based cohort study using data from regional health information systems (HIS). We included dementia patients aged ≥65 years residing in the Lazio region. The exposure was defined as new use vs non-use of APs. Dementia patients with incident use of APs during 2015 were followed-up from the date of first prescription to the earliest among discontinuation of use, death, or end of study (December 31, 2016). RESULTS: We enrolled 24,735 dementia patients, 1727 (6.7%) new users and 23,008 non-users of APs. Forty-four percent of AP users were treated for more than 3 months, and among these about 60% received APs continuously for at least 12 months. Individuals using antidepressant or anti-dementia drugs had higher odds of being prescribed with APs (OR: 1.67 and OR: 1.86, respectively). Patients exposed to polypharmacy were less likely to receive APs (OR: 0.82). Cardiovascular risk factors and comorbidities were not associated with APs use. Low socio-economic position was associated with lower odds of atypical AP prescribing (OR: 0.57). CONCLUSION: The study showed that a not negligible proportion of patients had a period of AP use longer than recommended by guidelines. We identified socio-demographic and clinical factors associated with first use of APs, providing insight into prescribing practices in a community setting and useful information to address areas of potential inappropriateness.